2012
DOI: 10.1021/je2012814
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Plant Biomass Components. Heat Capacity, Combustion Energy, and Gasification Equilibria of Lignin

Abstract: Heat capacities and enthalpies of formation were determined for two samples of lignin obtained from rape straw by different methods. The obtained experimental results allowed us to obtain the values of thermodynamic properties for this material. The equilibria of the processes of lignin gasification were considered. The adiabatic temperatures of the gasification and energetic characteristics of the products of lignin thermolysis were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 7 publications
3
30
0
Order By: Relevance
“…4 can be applied to determine the degree of reduction of SOM, γ C , also shown in Table 1. All L/F samples have γ C values close to those of carbohydrates (γ C = 4) and tend to increase from the top soil layer to the mineral samples where values show SOM more reduced than carbohydrates, approaching to values reported for lignocellulosic material and lignin in some of the H and M samples (Gary et al 1995, Voitkevich et al 2012). Therefore, the degree of reduction of SOM in the mineral soils is higher than those in the surface organic layers with little variability among sampling sites for the L/F layer, and more spatial variability in the H and M soils.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…4 can be applied to determine the degree of reduction of SOM, γ C , also shown in Table 1. All L/F samples have γ C values close to those of carbohydrates (γ C = 4) and tend to increase from the top soil layer to the mineral samples where values show SOM more reduced than carbohydrates, approaching to values reported for lignocellulosic material and lignin in some of the H and M samples (Gary et al 1995, Voitkevich et al 2012). Therefore, the degree of reduction of SOM in the mineral soils is higher than those in the surface organic layers with little variability among sampling sites for the L/F layer, and more spatial variability in the H and M soils.…”
Section: Resultsmentioning
confidence: 65%
“…Δ C H SOM has been rarely used as a SOM property due to technological reasons, but new DSC devices can measure simultaneously the energy and mass losses, improving accuracy and yielding Q SOM values close to the heat of combustion of organic material reported by the literature (Gary et al 1995, Villanueva et al 2011, Voitkevich et al 2012 and to values from mineral soils reported recently (Barré et al 2016, Barros et al 2016, Barros 2018. Calculation of Δ C H SOM yields the possibility to quantify SOM recalcitrance by the degree of reduction, γ C .…”
Section: Discussionmentioning
confidence: 92%
“…For instance, one study shows that amorphous cellulose would have a b-relaxation intensity of 4-5 times greater than that for wood cellulose with 67 % crystallinity [28]. Thus, while crystalline cellulose might Table 2 Group vibrations in the 400-4000 cm -1 range assigned by experimental infrared and Raman spectroscopic studies [21,[42][43][44][45][46][47][48][49] Vibration mode Wavenumber (cm - Based on data from [30,[32][33][34][35] for the range 1-200 K a The skeletal contribution for amorphous wood cellulose was evaluated both by fitting Eq. (6) to experimental data in the 80-200 K range and using Debye temperatures for microcrystalline cotton cellulose experience an increase in conformational motion, this effect is considerably greater for amorphous cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…3 Calculated and experimental c p for a-d cellulose of various origin, and e, f lignin extracted by two different methods. Based on data from a-c [30], d [31], e, f [35] motion. The external contribution is as for the other compounds found by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The valuation of this bioresource is relatively interesting because lignin is the second component represented in the biomass after cellulose. Unfortunately, it has long been used as a fuel owing to its high calorific value (Voitkevich et al, 2012). Future research will help develop leads for the valuation of lignin.…”
Section: Affordable Bioproducts and Biofuelsmentioning
confidence: 99%